2003
DOI: 10.1034/j.1600-0781.2003.00052.x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation of (+)‐catechin protects against UVB‐induced skin damage by modulating antioxidant enzyme activities

Abstract: These results demonstrate that dietary supplementation with (+)-catechin could protect epidermal cells against UVB-induced damage by modulating antioxidant enzyme activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
1

Year Published

2005
2005
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 27 publications
1
31
0
1
Order By: Relevance
“…In light of this, it is interesting to note that pomegranate juice has a significant antioxidant capacity (51,61). Glutathione is a well-characterized reactive nitrogen and oxygen species scavenger in the brain, and catechins (another constituent of pomegranate juice) have been shown to increase intracellular glutathione levels and modulate glutathione peroxidase activity (62)(63)(64)(65). Catechins also modulate tyrosine kinase and protein kinase C signal transduction pathways in vitro (30,66 -69).…”
mentioning
confidence: 99%
“…In light of this, it is interesting to note that pomegranate juice has a significant antioxidant capacity (51,61). Glutathione is a well-characterized reactive nitrogen and oxygen species scavenger in the brain, and catechins (another constituent of pomegranate juice) have been shown to increase intracellular glutathione levels and modulate glutathione peroxidase activity (62)(63)(64)(65). Catechins also modulate tyrosine kinase and protein kinase C signal transduction pathways in vitro (30,66 -69).…”
mentioning
confidence: 99%
“…Feeding RPO alone did not show any significant effect on either GSH level or the GSH/GSSG ratio. The increased GSH level may be ascribed to the ability of flavonoids in rooibos to increase GSH synthesis by upregulating the mRNA expression of γ-glutamylcysteine synthetase (γ-GCS), the rate limiting enzyme in the GSH biosynthetic pathway, since previous studies have shown that polyphenolic compounds from plants increased the γ-GCS activity and GSH contents (Jeon et al, 2003;Chen et al, 2004;Moskaug et al, 2005) and the rooibos extract has a significantly higher total polyphenol content when compared to the RPO in the current study. In the liver, feeding rooibos, RPO or their combination for 22 weeks did not show any effect on the GSH level, however GSSG level was significantly reduced in the rooibos alone or the combination group resulting in an increased GSH/GSSG ratio in this groups.…”
Section: Discussionmentioning
confidence: 82%
“…Another intriguing possibility for the observed GSH increase is that rooibos polyphenols may upregulate the expression of -glutamylcysteine synthetase ( -GCS), which is the rate limiting enzyme in the synthesis of GSH. Previous studies have shown that polyphenolic compounds from plants increased the -GCS activity and GSH contents [110][111][112], although no study has yet been conducted to determine if rooibos or its flavonoids can increase -GCS mRNA expression. That RPO supplementation restored the observed impairment in the redox status observed in t-BHP challenged rat could be ascribed to its vitamin E and carotene constituents.…”
Section: Discussionmentioning
confidence: 99%